MATERIAL KOMPOSIT POLIMER TAHAN BALISTIK UNTUK APLIKASI HELM MILITER DALAM MENDUKUNG MATERIAL PERTAHANAN INDONESIA - Mahyaruddin Mrp; Sovian Aritonang (POLITALA PRESS, 2022)
Polymer composites are widely used in military applications. In this instance, to shed light on polymer composites and their uses in the field of defense, particularly ballistic ones. Military vests, personnel helmets, and other items that need to be made of ballistic-resistant materials but are still lightweight and reasonably priced, fall into three general categories. When it comes to enhancing the mobility of military forces, composite materials have outperformed metal materials in military applications. Given the speed of approaching bullets, it is crucial that military helmets contain composite materials, one of which is constructed of thermoplastic polymers and thermosets. Utilizing a bullet and a new polymer composite (UHMWPE) with a weight of 1000 g one suitable material for use in military bulletproof helmets is one with a speed of 600 m/s.